The Effects of an Eight-week Cawthorne-Cooksey Training Program on Balance and Lower Limb Strength in the Elderly - Mohammad Javad Azimizadeh; Seyyed Mojtaba Tabatabai Asl; Seyyed Hosein Hoseini (Biyumikānīk-i varzishī)
Objective: With age, the problems associated with loss of balance, followed by decreased muscle strength and physical function, increase. Therefore, the elderly are exposed to serious injuries. Therefore, the aim of the present study was to investigate the effect of Cawthorne Cooksey training on balance and lower limb strength in the elderly. Methods: Subjects including 24 elderly men and women participated in this study voluntarily and were divided into experimental groups (n‌=‌12) and control (n‌=‌12). The design of the present study was pre-test and post-test. Cawthorne Cooksey training were performed for eight weeks, three sessions per week and each session for 60 minutes. The main variables were balance and lower limb strength, and the leaf test was used to assess balance and the rise and fall test was used for lower limb strength. One-way covariance and dependent t-test in SPSS software version 26 were used to analyze the pre-test and post-test results and compare the groups. Results: The results of this study showed that the balance in the experimental group had a significant improvement compared to the control group (P‌=‌0.001). There was also a significant difference in lower limb strength in the experimental group compared to the control (P‌=‌0.002). Conclusion: According to the findings of this study, these exercises positively affect balance and lower limb strength in the elderly. Due to the decline in physical function of the elderly, performing these exercises increases the level of physical function and quality of life of the elderly.